BATAS AMBANG PENCALONAN PRESIDENTIAL THRESHOLD YANG SEHARUSNYA 0% - Miasiratni Miasiratni (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Presidential Threshold as the threshold for the vote acquisition that must be obtained by political parties in an election to be able to nominate a presidential candidate. The rule for the presidential nomination threshold (presidential threshold) of 20%-25% in the Law on the Implementation of General Elections, is the result of a product of democracy in the House of Representatives. The 20 percent presidential nomination threshold should be being challenged to the Constitutional Court (MK) with the hope of being zero percent. It is believed that the zero percent presidential threshold will not bring up hundreds of presidential candidates. The requirements for presidential candidacy have been regulated in the 1945 Constitution, which is carried out by political parties. The provisions regarding the number of seats and the number of valid national votes that are a requirement to be able to nominate pairs of candidates for president and vice president always change every time an election is held. In the 2019 general election, the regulation regarding the Presidential Threshold is based on the provisions contained in Article 222 of the Election Law which states that: Candidate pairs are proposed by a political party or coalition of political parties participating in the election who meet the requirements for obtaining seats of at least 20% (twenty percent) of the total number of seats. the number of seats in the DPR or obtain 25% (twenty five percent) of the nationally valid votes in the previous election for members of the DPR.Keywords: Nomination Threshold, Presidential Threshold.